Analysis of The Effect of Employee Placement and Environment on Performance through Motivation - Mariani Setyowati; Harsono Harsono; Tanto G. Sumarsono (Syntax Corporation Indonesia, 2020)
This study aims to describe the placement of employees, work environment, motivation and performance as well as analyzing its influence on the Civil Servants of Balai Besar Pemerintahan Desa in Malang. The study was conducted by using descriptive analysis and path analysis with a significance level (?) 0.05. Samples taken were civil servants at the Balai Besar Pemerintahan Desa in Malang with a total of 31 people. The results showed that the placement of employees and the work environment had a positive and significant effect on motivation indicated by coefficients of 0.518 and 0.756 and sig 0.005 and 0.010. Employee placement and work environment had a positive and significant effect on performance with coefficients of 0.735 and 0.764 and sig values ??of 0.000 and 0.001. Motivation had a positive and significant effect on performance with a coefficient of 0.989 and sig 0,000. Motivation had not been able to mediate the effect of employee placement and work environment on performance. This is because the results of the value of the direct effect was greater when compared to the indirect effect. Keyword: Employee Placement, Work environment, Motivation and Work performance